Is this crisis of French socialism different? Hollande, the rise of Macron, and the reconfiguration of the left in the 2017 presidential and parliamentary elections. (2nd October 2017) - Clift, Ben; McDaniel, Sean
Abstract: With the extraordinary rise of Emmanuel Macron and the near complete collapse of the Parti Socialiste (PS), the past year has seen arguably the most dramatic upheaval in the French party system since 1958. This article develops a political economy analysis of the Hollande quinquennat to better understand how we arrived here. It argues that Hollande's programmatic failures must be situated within an institutional account of the constraints of the presidential logic of the Fifth Republic and tensions between competing factional courants within the Socialist Party. Here we shed fresh light on this moment of rupture by situating a political economy analysis of Hollande's economic programme within a more intricate institutional analysis of the specificities of the PS and its position within the Fifth Republic. The article traces the most salient political developments of the 2017 elections and outlines the political landscape of the contemporary French left. These factors explain why, after numerous crises of French socialism, this time is different.